2015
DOI: 10.1093/nar/gkv911
|View full text |Cite
|
Sign up to set email alerts
|

The STAT3 HIES mutation is a gain-of-function mutation that activates genes via AGG-element carrying promoters

Abstract: Cytokine or growth factor activated STAT3 undergoes multiple post-translational modifications, dimerization and translocation into nuclei, where it binds to serum-inducible element (SIE, ‘TTC(N3)GAA’)-bearing promoters to activate transcription. The STAT3 DNA binding domain (DBD, 320–494) mutation in hyper immunoglobulin E syndrome (HIES), called the HIES mutation (R382Q, R382W or V463Δ), which elevates IgE synthesis, inhibits SIE binding activity and sensitizes genes such as TNF-α for expression. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
3
8
1
Order By: Relevance
“…In the GAS-luciferase reporter assay, STAT4 responded to LIF, resulting in GAS-dependent luciferase reporter activation ( Fig 5E). We tested individual S-to-A mutants of STAT4 and noted that in HEK293T cells, the S713A mutant exhibited enhanced GAS-luciferase reporter activity (Fig 5F), in agreement with the findings that S713 phosphorylation dissociates STAT4 from LIFR, as shown in Fig 4G. We previously reported that STAT3 not only binds to the canonical SIE "TTCXXXGAA" but also binds to the AGG element "AGGXXXAGG" (Xu et al, 2015). We tested individual S-to-A mutants of STAT4 and noted that in HEK293T cells, the S713A mutant exhibited enhanced GAS-luciferase reporter activity (Fig 5F), in agreement with the findings that S713 phosphorylation dissociates STAT4 from LIFR, as shown in Fig 4G. We previously reported that STAT3 not only binds to the canonical SIE "TTCXXXGAA" but also binds to the AGG element "AGGXXXAGG" (Xu et al, 2015).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…In the GAS-luciferase reporter assay, STAT4 responded to LIF, resulting in GAS-dependent luciferase reporter activation ( Fig 5E). We tested individual S-to-A mutants of STAT4 and noted that in HEK293T cells, the S713A mutant exhibited enhanced GAS-luciferase reporter activity (Fig 5F), in agreement with the findings that S713 phosphorylation dissociates STAT4 from LIFR, as shown in Fig 4G. We previously reported that STAT3 not only binds to the canonical SIE "TTCXXXGAA" but also binds to the AGG element "AGGXXXAGG" (Xu et al, 2015). We tested individual S-to-A mutants of STAT4 and noted that in HEK293T cells, the S713A mutant exhibited enhanced GAS-luciferase reporter activity (Fig 5F), in agreement with the findings that S713 phosphorylation dissociates STAT4 from LIFR, as shown in Fig 4G. We previously reported that STAT3 not only binds to the canonical SIE "TTCXXXGAA" but also binds to the AGG element "AGGXXXAGG" (Xu et al, 2015).…”
supporting
confidence: 87%
“…As expected, STAT4-DSP had stronger transcriptional activity than full-length STAT4 in response to LIF treatment ( Fig 5E), suggesting that SPXX phosphorylation plays a negative regulatory role in STAT4 activity. We tested individual S-to-A mutants of STAT4 and noted that in HEK293T cells, the S713A mutant exhibited enhanced GAS-luciferase reporter activity (Fig 5F), in agreement with the findings that S713 phosphorylation dissociates STAT4 from LIFR, as shown in Fig 4G. We previously reported that STAT3 not only binds to the canonical SIE "TTCXXXGAA" but also binds to the AGG element "AGGXXXAGG" (Xu et al, 2015). In STAT3-null mouse embryonic fibroblasts (MEFs) cotransfected with STAT4 and STAT3, STAT4 further inhibited STAT3 activity during SIE-driven or AGG element-driven luciferase reporter activation ( Fig 5G and H).…”
supporting
confidence: 87%
“…To identify the exact binding element(s) of STAT3 on NMDAR promoters, we constructed GAS promoter elements in NMDAR promoter regions for luciferase activity assay. As the speci c sequence of the GAS element for STAT1 is TTC(N2-4)GAA, and for STAT3 is TTC(N3)GAA [26,27], we observed only one conserved GAS promoter element for STAT3 binding in the promoter regions of GluN1, GluN2B or GluN2A, though there are 2 conserved GAS promoter elements for STAT1 binding in the promoter regions of GluN1…”
Section: Discussionmentioning
confidence: 71%
“…Intracellular P301L-hTau accumulation inactivates STAT3 despite the level of phosphorylated STAT3 increases In our previous study, we found that the accumulated htau increased STAT1 activity, while the activity of HNF1, HOX4C, PLAG1, SMUC, VDR, SF-1 and PIT1 decreased remarkably [24]. STAT3 and STAT1 belong to the STAT protein family, and both are reported to be involved in cognitive functions [25][26][27][28][29][30][31][32]. Herein, we investigated the effects of P301L-hTau accumulation on STAT3 activity, and if so, the role of STAT3 in P301L-hTau-induced cognitive de cits and the underlying molecular mechanisms.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation